Elements for Adapting Math Tests to Screen Reader Users - Ordoñez, Graciela (2021)
The objective of the study was to assess items from the standardized test quantitative mathematical skills content database, in order to adapt them and make them accessible to visually impaired individuals who use screen readers. A qualitative and hermeneutic-dialectic, design methodology was used, thereby facilitating the discovery and interpretation of explanations, in-depth interviews with experts to adjust the test items to the screen readers. The study results primarily uncover the importance of analyzing how mathematical symbols and expressions are read and interpreted when using a screen reader.